In Situ TEM Observation of Electron‐Beam‐Induced Microstructural Evolution in van der Waals Layered Magnetic CrSBr Semiconductor - Hao‐Wen Deng; Yi‐Tang Tseng; Mu‐Pai Lee; Yen‐Fu Lin; Wen‐Wei Wu (Advanced Electronic Materials, 2023)
Abstract CrSBr is a recently developed 2D van der Waals (vdW) magnet. However, this development is still in its infancy, and hence, there has been limited relevant research so far. In this study, ultrathin CrSBr is first prepared via blue‐tape‐based mechanical exfoliation. Subsequently, Raman and X‐ray photoelectron spectroscopy analyses are performed to obtain detailed information on the chemical structure. The thickness of most exfoliated samples measured using atomic force microscopy (AFM) is ≈1.6–6.5 nm corresponding to 2–8 layers. Notably, high‐resolution images of CrSBr atomic structures are seldom observed using transmission electron microscopy (TEM). Atomic‐thick CrSBr is extremely beam‐sensitive, and hence, it is easily damaged under e‐beam irradiation. Nevertheless, e‐beam damage provides an opportunity to study the structural properties of CrSBr. Different types of knock‐on effects are recorded and further analyzed using atomic‐scale imaging. Furthermore, the high‐resolution TEM images show that the unique atomic stepped boundary is consistent with the orthorhombic slip system. The recrystallization process of CrSBr and the formation/refilling of the nanoholes are recorded via in situ TEM. These findings deepen the understanding of the fundamental insight into 2D vdW magnetic semiconductors and pave the way for next‐generation spin‐based electronics.